2021
DOI: 10.1021/acsami.1c17232
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Thermochromic Luminescent Fibers Controlled by Self-Crystallinity Phase Change for Advanced Smart Textiles

Abstract: Smart textiles with tunable luminescence have received special attention due to their great potential in various advanced photonic applications. Particularly, the development of one-dimensional, on-demand, responsive fluorescence fibers with excellent adaptability is of great significance. Herein, we propose electro-thermochromic fluorescence fibers regulated by a self-crystallinity phase change; that is, their tunable luminescence properties are derived from the reversible conversion of the dispersion state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…[75] The synergy arising from the use of CNTs and Fe 3 O 4 resulted in an improved EMI shielding effectiveness (Figure 3l). In addition to the aforementioned impressive functionalities, PCMs can be employed as superhydrophobic TES coatings [77] or crucial components for tunable luminescent materials [78] and highly efficient infrared stealth counterparts. [79,80] The integration of PCMs with thermal insulation materials is feasible for thermal camouflage and stealth technology.…”
Section: Multifunctional Pcmsmentioning
confidence: 99%
“…[75] The synergy arising from the use of CNTs and Fe 3 O 4 resulted in an improved EMI shielding effectiveness (Figure 3l). In addition to the aforementioned impressive functionalities, PCMs can be employed as superhydrophobic TES coatings [77] or crucial components for tunable luminescent materials [78] and highly efficient infrared stealth counterparts. [79,80] The integration of PCMs with thermal insulation materials is feasible for thermal camouflage and stealth technology.…”
Section: Multifunctional Pcmsmentioning
confidence: 99%
“…12−16 The research related to nanofibrous membranes with new thermochromic functions is identified as a prospering topic. 17−21 Reversible thermochromic fibers are widely used in many fields such as smart textiles, 18,22,23 thermally responsive sensors, 7,24 and color indicators. 25−27 Recently, reversible thermochromic phase change material (RTPCM) systems based on a luminescent dye or leuco dye have been selected as core 28−31 solutions to prepare temperature-sensitive thermochromic fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Phase change materials (PCMs) are special energy materials that can absorb and release a large amount of heat during the process of physical state change. The research related to nanofibrous membranes with new thermochromic functions is identified as a prospering topic. Reversible thermochromic fibers are widely used in many fields such as smart textiles, ,, thermally responsive sensors, , and color indicators. Recently, reversible thermochromic phase change material (RTPCM) systems based on a luminescent dye or leuco dye have been selected as core solutions to prepare temperature-sensitive thermochromic fibers. The reversible thermochromic phase change material system mainly consists of three elements: electron donor (GN-2), electron acceptor (bisphenol AF, BPAF), and organic solvent ( n -butyl stearate).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to uniform color tuning when using a continuous film heater, patterned colors appear when locally heating a thermochromic system using patterned electrodes. Despite the promising studies on electrothermally driven photonic devices, a major challenge in this field is the development of simultaneously flexible and transparent photonic systems with multicolor tuning, vitally important for effective display and window applications. Most reports on electrochromic devices make use of temperature-responsive pigments, which can only be switched between colored and discolored states when applying an electrothermal stimulus and are limited to nontransparent devices due to their low optical quality. , Recent progress has led to the realization of electrothermally driven structural color-tunable systems, but these are limited to either rigid transparent , or flexible nontransparent devices due to the poor mechanical or optical properties of at least one layer in the final material. Additionally, scaling up to large-area applications remains rather difficult since scalable processes to develop such multilayered photonic foils have been rarely reported. ,, To establish an electrothermally driven structural colored system featuring both high transparency and flexibility, a flexible, transparent heater must be integrated.…”
Section: Introductionmentioning
confidence: 99%